2011
DOI: 10.4187/respcare.01169
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning the Respiratory Therapy Workforce for 2015 and Beyond

Abstract: SummaryThe American Association for Respiratory Care established a task force in late 2007 to identify likely new roles and responsibilities of respiratory therapists (RTs) in the year 2015 and beyond. A series of 3 conferences was held between 2008 and 2010. The first task force conference affirmed that the healthcare system is in the process of dramatic change, driven by the need to improve health while decreasing costs and improving quality. This will be facilitated by application of evidence-based care, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 6 publications
0
54
0
Order By: Relevance
“…These conferences rolled out over a number of subsequent years, and a summary of their proceedings was published in RESPIRATORY CARE. [12][13][14] Table 8 provides a summary of the conferences objectives. 12 In the second AARC conference in the "2015 and Beyond" series, the participants identified a grouping of respiratory care competencies that would be necessary for future graduates and those practicing in the profession.…”
Section: The Future Of Respiratory Carementioning
confidence: 99%
“…These conferences rolled out over a number of subsequent years, and a summary of their proceedings was published in RESPIRATORY CARE. [12][13][14] Table 8 provides a summary of the conferences objectives. 12 In the second AARC conference in the "2015 and Beyond" series, the participants identified a grouping of respiratory care competencies that would be necessary for future graduates and those practicing in the profession.…”
Section: The Future Of Respiratory Carementioning
confidence: 99%
“…We are indeed facing tremendous challenges and opportunities in the future, and it is prudent that educators review all 3 conference findings that have been published in RESPIRA-TORY CARE. [92][93][94] As we move our profession forward we will no doubt face challenges, and thoughtful transition is required so that RTs will be at the top of their game when caring for patients in the future. 91 Barnes et al 90 reported results of a survey of respiratory care educational program directors regarding the ability of the current educational infrastructure to make the necessary changes to prepare graduates who possess the qualifications identified for competent respiratory care providers in the future.…”
Section: Educationmentioning
confidence: 99%
“…[1][2][3] One of the competencies in the area of critical care was declared as the ability to "apply to practice all ventilation modes currently available on all invasive and noninvasive mechanical ventilators, as well as all adjuncts to the operation of modes." 2 Kacmarek 4 recently published a paper discussing the expectations of this future RRT regarding mechanical ventilation competencies.…”
Section: Introductionmentioning
confidence: 99%